Pelaksanaan Hukum Waris Perdata Barat (BW) dalam Praktik Musyawarah Keluarga pada Pembagian Warisan di Indonesia - Rayi Kharisma Rajib; Jan Crisando Saragih Sumbayak (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The implementation of Western Civil Inheritance Law based on the Burgerlijk Wetboek (BW) in Indonesia is often carried out through family deliberation. Although BW normatively regulates inheritance distribution, heirs generally prioritize mutual agreement to maintain family harmony. This study aims to analyze the application of BW inheritance law in the practice of family deliberation in inheritance distribution in Indonesia. The results show that family deliberation is more commonly chosen because it is considered capable of creating a fair and peaceful settlement while preventing disputes among heirs without disregarding applicable legal provisions.